Manajemen Penangkaran Lebah Madu (Apis Cerana Fabr.) di Desa Buana Sakti Kecamatan Batanghari Kabupaten Lampung Timur - Apriyanita Pitri Ningrum; Rudi Hilmanto; Wahyu Hidayat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
Honey forest are one of beekeeping product that can developed by honey bees breeding method.In order to remain sustainable production of honey breeding, agood breeding management is significantly needed. The purpose of this research was to identify and evaluate the breeding management of Apis cerana Fabr. honey bee based onthe indicator and parameter assessment of technical requirement planning, the technique, the implementation, and the products of breeding. This research was conducted from February 2012 until April 2012 in the Buana Sakti Village, District of Batanghari, East Lampung. The method used in this research is field observations and questionnairy interviews. The analysis applied in this reseacrh is quantitative and qualitative method, comparing the data collection from the field to the criteria and indicator of breeding management assessment. The results of this research showed that the aspect of technical requirement planning and the breeding products are considered good, it is because it has accomplished the requirement. While the aspect of breeding technique and implementation are considered not good, it is caused by the limited competence of bee farmer and the breeding methods. Overally, the breeding management of Apis cerana Fabr. honey bee in Buana Sakti village for all aspects is considered good. The breeding management of Apis cerana Fabr. honey bee in Buana Sakti village needs to be well improved, particularly in term of technique and implemetation of breeding to obtain the maximum quality of honey bee breeding. Keywords : Apis cerana Fabr., bee breeding management, bee conservation